From Biostimulant to Possible Plant Bioprotectant Agents (Agricultural Engineering, 2023)
Aqueous extracts of plants with proven biostimulant activity may have the potential to inhibit the growth and development of plant diseasecausing fungi. The potential use of extracts in such a role has many advantages including the fact that extracts are biodegradable, less costly, and readily available. Therefore, the aim of this study was to evaluate the potential of aqueous infusions, decoctions, and macerates extracted from burdock roots, wormwood leaves, lovage roots, flax seeds, and mullein flowers as bioprotectants. This study was carried out by testing in vitro the ability of these bioprotectants to inhibit the growth of the fungi Thielaviopsis basicola (Berk. and Broome), and Fusarium avenaceum (Fr.) Sacc, Fusarium culmorum (Wm.G. Sm.) Sacc., Fusarium sambucinum (Fuckel), Fusarium solani (Mart.) Sacc., Rhizoctonia solani (J.G. Kühn), Botrytis cinerea Pers., Sclerotinia sclerotiorum (Lib. de Bary), causing disease in soybean. The antifungal activity of macerates, infusions, and decoctions determined by the diffusion method in Petri dishes with solid PDA medium showed the potential of the tested aqueous extracts as bioprotectants able to inhibit the growth of fungi, causing soybean diseases.